Identification and Relative Growth of Prawns from the Sibam River, Pekanbaru, Riau - Gita Valentina Ginting; Deni Efizon; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractSibam River is inhabit by small sized prawns. Scientific information of those organism, however, is almost none. To understand the types of prawns present that area, a research has been conducted from April to May 2017. There were 3 sampling areas, in the upstream (St I), the middle area (St II), an in the downstream (St III). Prawns sampling were conducted once/week for a month period, using a scoop net (mesh size 0.5 cm). Morphometrical and meristical characteristics of the prawns were analyzed descriptively and te prawns sampled were identified. There were 65 palaemonids prawns captured and they were identifed Macrobrachium. Detail identification showed that they were Macrobrachium mammilodactylus (15 specimens, 9 males and 6 females) and Macrobrachium heterorhynchos (50 specimens, 6 males and 44 females). M. mammilodactylus charactererized by schapocherite length that is shorter than rostrum length, 7-18 teeth in the dorsal and 2-6 teeth in the ventral of rostrum, all segments except fingers with abundant short mammiliform protective setae. M. heterorhynchos charactererized by carapace and glabrous abdomen, without microspinules. In males, rostrum one-third distal extending beyond scaphocerite, 8-9 teeth in the dorsal and 4 teeth in the ventral. In female, rostrum just reaching end of schapocerite, 8 teeth in the dorsal and 5 teeth in the ventral.Keywords: Sibam River, freshwater prawns, Macrobrachium mammilodactylus, Macrobrachium heterorhynchos